PROGRAM PENGELOLAAN PESISIR DAN PPK KEGIATAN DED PENINGKATAN STATUS PPI PULAU BAAI PROVINSI BENGKULU - As ad As ad (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2019)
With the increase in PPI development Changes in social interactions that will be experienced by the people of Sumber Jaya Village occur because of fish traders who come from outside the village or even from outside the city of Bengkulu who come to PPI Baai Island to buy fish from collectors. In addition, changes in social interactions that occur in the midst of the community of Sumber Jaya Sub-District are a conflict between residents of Sumber Jaya Village and Andon fishermen who come from out of town and even outside the island. While in terms of economy, these changes will be seen from the amount of labor absorption that occurs around the location of the Baai Island PPI in the city of Bengkulu. The coastal community around PPP Pulau Baai is optimistic that it will experience a change towards the good with the increase in Baai Island PPI. Because the community of Sumber Jaya sub-district itself will feel there is a change in the area that used to be quiet now becomes more crowded. In addition, according to the Sumber Jaya village community itself who works as a fisherman, an increase in the development of the Baai Island PPI is expected to facilitate fishermen in carrying out activities before or after going to sea compared to the development of Baai Island PPI where fishermen had to spend more energy. With the development and improvement of the status of Baai Island PPI the number of people from outside the coastal area of ??Sumber Jaya Sub-District who came both in the purpose of buying and selling as well as andon fishermen would influence the social interaction of the surrounding coastal communities. In this case the change will lead to positive and negative aspects.